Experiences of street harassment and associations with perceptions of social cohesion among women in Mexico City - Paola A Campos; Kathryn L Falb; Sara Hernández; Claudia Díaz-Olavarrieta; Jhumka Gupta (Instituto Nacional de Salud Pública, 2017)
Objective. To document the frequency and forms of street harassment and examine the association between street harassment experiences and perceptions of social cohesion. Materials and methods. Baseline survey data collected among women seeking care in public health clinics in Mexico City were used for analysis. Results. Nearly two-thirds (62.8%) of women reported experiencing some form of street harassment in the prior month; women with street harassment experiences reported significantly lower perceived social cohesion (b=-0.46; 95%CI:0.69,-0.22). Conclusions. Findings indicate reducing street harassment may have important implications for improving women's perceived social cohesion and their safety in Mexico City.